Tuning of Ball and Beam System using Cascade Control - Somnath Garai; N.H.Balasubramanyam (International Journal of Engineering and Management Research, 2020)
This project presents a new strategy to approach cascade control tuning by using image processing and machine learning to generate required control parameters to be set into the controller. For test bed purpose a ball balance upon a horizontal beam is used which is actuated with a stepper motor, angle of the balance to be scanned by a camera and analyzed using python alongside an ultrasonic sensor to measure real time distance to the ball, set point to be set by user and control action generated upon generating required information from hardware frame.